2020
DOI: 10.1093/ndt/gfaa142.p0176
|View full text |Cite
|
Sign up to set email alerts
|

P0176regulation of Oxalate Homeostasis by Oxalate-Degrading Activity in Fecal Microbiota in Dialysis Patients

Abstract: Background and Aims Despite evidence suggesting that a lack of fecal oxalate-degrading bacteria colonization is a risk factor for calcium oxalate stone formation, little is known about the oxalate-degrading activity (ODA) in fecal microbiota in end-stage renal disease (ESRD) patients. In addition, to date, there has been a general lack of research on the effect of fecal ODA on oxalate homeostasis in dialysis patients. The present pilot cross-sectional study was performed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Since the gut microbiota in patients on dialysis is characterized by increased Enterobacteriaceae and low colonization of Bifidobacterium and Lactobacillus species compared with normal controls (Hu et al, 2020;Ren et al, 2020), the low abundance of ODB in gut microbiota may play a significant role in oxalate homeostasis in patients with ESRD. Indeed, we previously demonstrated that the ODB number in patients on dialysis was significantly lower than in healthy volunteers (Stepanova et al, 2020a;. However, when we separately evaluated the ODB number and their total ODA in fecal microbiota in patients on dialysis, we got surprising results.…”
Section: Gut Microbiota Disruption Causes Hyperoxalemia In Patients With Esrdmentioning
confidence: 85%
“…Since the gut microbiota in patients on dialysis is characterized by increased Enterobacteriaceae and low colonization of Bifidobacterium and Lactobacillus species compared with normal controls (Hu et al, 2020;Ren et al, 2020), the low abundance of ODB in gut microbiota may play a significant role in oxalate homeostasis in patients with ESRD. Indeed, we previously demonstrated that the ODB number in patients on dialysis was significantly lower than in healthy volunteers (Stepanova et al, 2020a;. However, when we separately evaluated the ODB number and their total ODA in fecal microbiota in patients on dialysis, we got surprising results.…”
Section: Gut Microbiota Disruption Causes Hyperoxalemia In Patients With Esrdmentioning
confidence: 85%
“…However, although CKD-associated gut microbiota alterations are highlighted in multiple recent publications [15][16][17], there is little evidence of the impact of CKD on the number and functional capacity of ODB. In our previous reports, we have demonstrated that oxalate homeostasis in CKD patients was influenced not so much by the quantity of ODB in the intestinal microbiota but by the total ability of different strains of ODB to metabolize oxalate [7,[18][19][20].…”
mentioning
confidence: 96%